2009
DOI: 10.1177/0044118x09333665
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in the Racial and Ethnic Socialization of African American Adolescents

Abstract: Scholars in the field of African American family studies recognize the influence of gender on socialization. However, few studies investigate how gender influences the racial and ethnic socialization of African American youth. To examine the role of gender (both caregiver and adolescent) in socialization practices, data were obtained from 218 African American adolescents attending a public high school in the northeastern United States. Participants reported on the socialization messages provided by their careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 41 publications
6
75
0
Order By: Relevance
“…Specifically, this investigation found that African American fathers were more likely to communicate these mes sages with their sons. Studies using adolescent-reports of parental socialization have provided some additional support for this gen der variation (e.g., Brown, Linver, & Evans, 2010). Still, an important gap in this literature has been the identification of racial socialization patterns among African American fathers as well as whether they vary their practices by child characteristics.…”
Section: Child Characteristics As Correlates Of Fathers' Racial Sociamentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, this investigation found that African American fathers were more likely to communicate these mes sages with their sons. Studies using adolescent-reports of parental socialization have provided some additional support for this gen der variation (e.g., Brown, Linver, & Evans, 2010). Still, an important gap in this literature has been the identification of racial socialization patterns among African American fathers as well as whether they vary their practices by child characteristics.…”
Section: Child Characteristics As Correlates Of Fathers' Racial Sociamentioning
confidence: 99%
“…Multiple studies have demonstrated that fathers have less frequent to occasional discussions regarding cross-racial interactions, and awareness of and coping with racial discrimination among fathers (Brown et al, 2009;Crouter et al, 2008). Investigations using adolescent reports of fathers' racial socialization have noted similar patterns across these dimensions (e.g., Brown, Linver, & Evans, 2010). Again, dimensions encom passing messages that promote cultural awareness and alert youth to potential racial barriers have been a primary focus of the existing literature.…”
mentioning
confidence: 99%
“…As noted above, research has found gender differences in coping strategies among adolescents, which may be related to subsequent anxiety symptoms as well. There may be within culture gender differences in parenting strategies and adolescents experience of racism, as some research suggests that African-American parents prepare their sons more for racism and challenging social events than they do their daughters (Brown, Linver, & Evans, 2010). This research seeks to explore the influence of gender and other variables on the expression of anxiety among adolescents.…”
Section: Gendermentioning
confidence: 99%
“…Families may perceive the racial landscape as differing in scope based on gender, and their R/ES practices may reflect these interpretations (Brown et al 2010). McHale et al (2006) noted that mothers and fathers socialize children differently based on age of the child (mothers provide racial socialization for younger children), and the child's gender (fathers focus on sons).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that boys and girls experience racial socialization differently, with girls more likely to receive messages about cultural pride or knowledge, and boys more likely to receive messages around preparation for racism (Hughes et al 2006;Stevenson et al 2002). However, research by Brown et al (2010) found that girls receive more racism awareness and cultural pride/knowledge messages than boys. The intersection of race and gender encounters for Black youth may result in variations of specific R/ES experiences.…”
Section: Introductionmentioning
confidence: 99%